Innovation, possibilities and limitations in the use of an eye tracker in science communication research: a study on the importance of the source of information in health news - Luís Amorim (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2021)
Our study, the result of an international partnership, sought to assess the importance given by 23 readers to the name of the publication source for four different texts on health topics, using an innovative methodology in the academic study field of scientific communication – an eye tracker. With an eye tracker, it is possible to map at every moment the reader’s eyes and points of fixation of the eye on the text, indicating the reader’s attention. Although the source of publication is considered an important criterion for the credibility of the information, our results, from the analysis of 35,394 measurements of fixations measured by the eye tracker, indicate the little importance given to the name of the publication source, even though the text presents fake news characteristics.